Enhancing Food and Nutrition Literacy: A Strategy to Reduce the Burden of Household Food Waste in Indonesia - Sofiany, Intan Rosenanda (BKM Public Health and Community Medicine, 2024)
Purpose: One-third of the world’s food production is wasted annually, leading to a growing global issue of food waste in both developed and developing countries. Indonesia is the second largest contributor of global food waste with 300 kg/person per year. The lack of effective food waste management policies could hinder the achievement of Sustainable Development Goal (SDG) 12.3., which aims to halve per capita global food waste at the retail and consumer levels by 2030. Currently, local and national programs have been launched to reduce this issue. However, the focus primarily lies on countermeasures. Complementing these efforts with upstream prevention is crucial, specifically by reducing the potential of food waste generated. Integrating food and nutrition literacy aspects as influential factors of food waste behaviour is important. Content: Integrating food and nutrition literacy aspects can be achieved by promoting smart shopping and mindful eating movements. This initiative should be shared widely via social media, Community Health Center (Puskesmas), and schools, by adapting the material according to the target audience. With these movements, communities will enhance their literacy skills. This will enable them to become more conscious of their shopping and food consumption habits, ultimately leading to a food waste reduction. However, this movement could encounter challenges due to the difficulty of measuring literacy level changes. The growing prevalence of social media users in Indonesia presents an opportunity to broaden the reach of the program. The food waste issue involves multiple interconnected factors. Identifying the root causes, such as low levels of food and nutrition literacy, can help solve this problem. Combating food waste by integrating food and nutrition literacy requires sustainable involvement and collaboration between government officials, health facilities, schools, and the community as the main actors.